The Influence of User-Generated Content on Brand Image on Social Media - Adhy Firdaus (PT. Hafasy Dwi Nawasena, 2025)
The development of social media has changed the paradigm of brand communication from a top-down approach to a more participatory model. User-generated content (UGC), which is content voluntarily generated by users, now plays a central role in shaping brand image in the digital space. This content is considered more authentic, credible, and influential than traditional advertising because it is based on real experiences and social interactions. In this context, consumers act as co-creators who are able to shape public opinion and influence brand perception collectively. However, the high dependence on UGC also presents strategic challenges, especially related to managing negative narratives and potential reputation crises. This study uses a qualitative approach with a literature study method to analyze the influence of UGC on brand image. Data were collected from various verified scientific sources in the last decade, and analyzed using qualitative content analysis techniques. The findings show that the effectiveness of UGC is greatly influenced by the authenticity, credibility, and emotional context of the message delivered. Therefore, brand communication strategies in the digital era need to transform to be more responsive, collaborative, and data-based in order to build consumer trust and create a sustainable brand image.